2009
DOI: 10.1088/0264-9381/26/15/155018
|View full text |Cite
|
Sign up to set email alerts
|

Hawking radiation of an apparent horizon in a FRW universe

Abstract: Hawking radiation is an important quantum phenomenon of black hole, which is closely related to the existence of event horizon of black hole. The cosmological event horizon of de Sitter space is also of the Hawking radiation with thermal spectrum. By use of the tunneling approach, we show that there is indeed a Hawking radiation with temperature, T = 1/2πr A , for locally defined apparent horizon of a Friedmann-Robertson-Walker universe with any spatial curvature, wherer A is the apparent horizon radius. Thus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
273
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(290 citation statements)
references
References 49 publications
14
273
1
2
Order By: Relevance
“…the field equations become T dS = dE + P dV ) continues to hold for a very wide class of theories! In the more general class of theories, one can define a natural entropy for the horizon called the Wald entropy [17] and we again get the same result with correct Wald entropy (for a sample of results see [18][19][20][21][22][23][24][25][26]). …”
Section: Gravitational Field Equations As a Thermodynamic Identitymentioning
confidence: 54%
“…the field equations become T dS = dE + P dV ) continues to hold for a very wide class of theories! In the more general class of theories, one can define a natural entropy for the horizon called the Wald entropy [17] and we again get the same result with correct Wald entropy (for a sample of results see [18][19][20][21][22][23][24][25][26]). …”
Section: Gravitational Field Equations As a Thermodynamic Identitymentioning
confidence: 54%
“…There are two definitions for the temperature of apparent horizon of FLRW universe [6-9, 15, 16], called the Hayward-Kodama temperature [6][7][8] and the Cai-Kim temperature [9,15], and both of them, whenever they are combined with the Bekenstein entropy relation, are in agreement with the Friedmann equation as well as the unified first law of thermodynamics. It is useful to note here that although the Bekenstein entropy is in line with the current accelerating phase of universe expansion and the second and generalized second laws of thermodynamics [17,18], some authors show that a dark energy candidate, due to its unknown nature, may modify the horizon entropy (the Bekenstein limit in the Einstein general relativity framework) [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to get a thermodynamic description of the universe evolution based on the Jacobson formalism, it has been shown that the choice of the cosmological apparent horizon as the holographic boundary [21,34] is more convenient. Such conclusion comes from that fact that, at the apparent horizon, the Friedmann equations have been shown to be equivalent to the first law of thermodynamics [47][48][49]. It occurs not only in Einstein's gravity, but in other scenarios such as braneworld models [50][51][52][53], Horava-Lifshitz gravity [54], Lovelock gravity [47,55] and f (R) gravity [56].…”
Section: Friedmann Equations From Thermodynamicsmentioning
confidence: 99%
“…which was obtained in the reference [48,49] through tunneling methods. From the equations above, we obtaiṅ…”
Section: Friedmann Equations From Thermodynamicsmentioning
confidence: 99%